Quản lí hoạt động giáo dục kĩ năng sống cho học sinh: Nghiên cứu tại một số trường tiểu học ở xã Bình Chánh, thành phố Hồ Chí Minh - Nguyễn Tiểu Phụng, Nguyễn Tiểu Phụng; Phạm Minh Giản, Phạm Minh Giản (Tạp chí Giáo dục, 2026)
In the context of comprehensive educational reform, life skills education for primary school students has become an essential requirement to foster the competencies needed for effective adaptation to modern social life. However, the management of life skills education activities in general education institutions-particularly in suburban areas such as Binh Chanh commune, Ho Chi Minh City-still faces considerable limitations in terms of awareness, organization, and implementation. This article presents the findings of a survey on the current status of managing life skills education activities for students in several primary schools in Binh Chanh commune. The results indicate that among the four management functions examined, the planning function was carried out relatively well, whereas the organization and monitoring-evaluation functions revealed notable shortcomings, especially in terms of coordinated implementation and quality assurance of life skills education. These findings provide practical evidence to inform the development of management measures aimed at improving the effectiveness of life skills education for primary school students, thereby meeting the requirements of holistic student development in the current period of educational renewal.